Participatory roles in community coalitions: Associations with perceptions of influence on decision-making. Issue 3 (27th May 2021) - Christens, Brian D.; Byrd, Kymberly; Hartigan, Lacey A.; Speer, Paul W.
ABSTRACT: Community-based coalitions seek to distribute leadership and decision-making broadly among participants to build capacity for improving local conditions. This is often difficult to achieve, however, due to a variety of structural and contextual factors. This study examines variance in decision-making influence among participants in 40 county-level substance abuse prevention coalitions. Participants' duration and frequency of involvement and the number of roles each member has played within the coalition were tested as predictors in multilevel regression models. Predictive values from the model show meaningful differences in perceived decision-making influence at the individual and coalition levels as participants take on additional roles. We also explore qualitative data on satisfaction with progress in coalitions with highest/ lowest levels of perceived influence in decision-making. Findings provide support for the concept of opportunity role structure, conceptualized as a component of organizational empowerment, and suggest strategies for building and assessing the capacity of community coalitions.